The Effectiveness of Videos in Teaching Grammar in EFL Classrooms The Case of First Year English LMD Students at Laghouat University - REGUIGUE, Fettoum; REMMACHE ,Kheira; GUELLIL, Assia (Faculty of Letters and Foreign Languages Department of English, 2017)
This study aims to find out some solutions to have a better learning. For decades learning foreign languages in classrooms has been regarded as failure. Thisfailureplaces itself especially in EFL classes. One of the major reasons that lead to that failure is grammar. Teaching grammar using classical ways is what pushes us to find new ways that suit this generation and this technology. Our focus in this research is to teach grammar using technology and in our case we are going to use videos. In this study, we are going to see how we can apply this method with first year students from the department of English in Ammar Telidji University. After that we will measure all the information found through the use of questionnaire. By the end of study, we expect to find that the use of videos in teaching grammar will be so beneficial and helpful to students as well as teachers. On the other hand, teachers’ role will decrease and the learners’ role will increase. In other words, the learning process will move from teacher centered toward more learner centered. This research is divided into three chapters, which would have all the answers for the use of this technique and how to apply it. Chapter one gives us all the definitions about this technique, and highlights all the weaknesses of the old techniques and let the readers see all the differences between the old techniques and our new technique, which is the use of videos. Chapter two leads the reader to the application of this technique; from the lesson plan toward grasping rules from videos. However, in chapter three the reader can find all the answers toresearch questions, students’ perception to this technique, their attitude, their role as well as teacher’s role. In addition to all the difficulties found in applying videos in classrooms . The findings obtained seem to indicate that teaching grammar through videos are advantageoustoolandworthwhile a technique to improve the learning process.